Embrija krimināltiesiskā aizsardzība - Rudzīte, Līva (Latvijas Universitāte, 2012)
Pētījuma ietvaros tiek apskatīta viena no pretrunīgākajām bioētikas nozarēm – eigēnika un tās apakšnozare gēnu inženierija, kuras attīstība ir radījusi nepieciešamību pārdomāt priekšstatus par to, ciktāl ir pieļaujami iejaukties cilvēka dzīves pamatnosacījumos. Darba mērķis ir izstrādāt pētījumu par embrija morālo statusu, tam piemītošajām tiesībām, kā arī pamatot embrija krimināltiesiskās aizsardzības nepieciešamību. Izpildot darbam izvirzītos uzdevumus, tiek secināts, ka embrijs unikālā ģenētiskā koda un potencialitātes dēļ, ir uzskatāms par personu ar tai piemītošajām tiesībām, kuras būtu aizsargājamas krimināltiesiski, kā arī būtu nepieciešams izstrādāt kriminālprocesuālo un civilprocesuālo mehānismu, kādā persona varētu aizsargāt savas aizskartās intereses. Darba gaitā tiek izstrādāta jauna Krimināllikuma norma, kurā ir noteikta embrija aizsardzība pret tā iesaistīšanu ģenētisku manipulāciju veikšanā, un veikta tās krimināltiesiskā sastāva analīze. Atslēgas vārdi: embrijs, tiesības, dzīvība, cieņa, eigēnika, gēnu inženierija, kriminalizācija.

The core focus of thesis is to examine one of the most controversial areas of bioethics – eugenics and its sub-sector genetic engineering whose development has created a growing necessity to consider perceptions how far intervention in the framework conditions of human life may be allowed. The main objective is to develop research on the moral status of embryo, on its inherent rights and to prove necessity for criminal protection of embryo. Fulfilling the tasks set to work, it is concluded that embryo because of the unique genetic code and of the potentiality is considered to be a person with inherent rights which would be necessary to protect with criminal remedies, as well as the need for criminal procedural and civil procedural mechanism by which a person can protect his own interests from violation. During the researh new form of criminal legislation is being developed, which defines the protection against embryo’s involvement in genetic manipulations, and carries out the criminal-composition analysis. Keywords: embryo, rights, life, dignity, eugenics, genetic engineering, criminalization. The core focus of thesis is to examine one of the most controversial areas of bioethics – eugenics and its sub-sector genetic engineering whose development has created a growing necessity to consider perceptions how far intervention in the framework conditions of human life may be allowed. The main objective is to develop research on the moral status of embryo, on its inherent rights and to prove necessity for criminal protection of embryo. Fulfilling the tasks set to work, it is concluded that embryo because of the unique genetic code and of the potentiality is considered to be a person with inherent rights which would be necessary to protect with criminal remedies, as well as the need for criminal procedural and civil procedural mechanism by which a person can protect his own interests from violation. During the researh new form of criminal legislation is being developed, which defines the protection against embryo’s involvement in genetic manipulations, and carries out the criminal-composition analysis. Keywords: embryo, rights, life, dignity, eugenics, genetic engineering, criminalization.
Criminal protection of embryos
Keywords: Juridiskā zinātne